Avaliação da gestão do sistema de esgoto sanitário de Santana do Livramento - RS - Pedroso, Claudio Ribeiro (2015)
The sustainability of quality of life in cities is related especially with the operating conditions of urban Sanitation Services. Environmental quality is a fundamental aspect for urban quality of life and public policies are increasingly attentive to the correct equation of collection and treatment of sewage services, the main component of urban sanitation. This paper analyzes the current state of the collection and treatment systems of Sewage of the city of Santana do Livramento-RS, which is located on the aquifer recharge zone of Guarani, reviews its current weaknesses in terms of operation and coverage of services sewage and also conformities management services in relation to the Municipal Legislation, State and Federal governing this area. The survey included the performance of the main system of collection and treatment current city, its central region, led to the Sewage Treatment Station - ETE's "Imhoff Park", designed in the 1920s and its suitability over the more than eighty years of operation. Were reviewed also detail the non-operational compliance and management of the services that are the responsibility of the Department of Water and Sewerage - DAE, Municipal Municipality created (reformatted) in 1969. We also assessed the prospects of the systems as a whole, identifying some factors that need more care in the evolution of these services. Existing data were used in a Municipal Sanitation Plan developed in 2009/2010. There was a lack of updated records, operating manuals, records and reliable statistical information. The management of the DAE Sanitary sewerage presented several nonconformities in relation to specific legislations in force and the Operating License of the ETE Imhoff Park. Affluent analysis, effluents and receiving body showed, in general, lower average percentages pollutant removal.